Computational design of improved two-photon active caging compounds based on nitrodibenzofuran - Dreuw, Andreas (Journal of computational chemistry, 2012)
Nitrodibenzofuran (NDBF) has recently been established as photolabile protecting group and efficiently used as two-photon active cage. In this work, a computational approach is exploited to rationally design improved two-photon active caging groups based on this NDBF chromophore. For this objective, first the two-photon absorption (TPA) properties of NDBF are investigated in detail and a suitable theoretical approach for the reliable simulation of TPA spectra of this class of compounds is identified. Then, virtual chemical modifications are performed by introduction of substituents at the chromophore and replacement of the central furan ring by pyrolle, thiophene, and borrole heterocycles.
Gesehen am 18.12.2017